Evaluation of Residual Compressive Strength and Behavior of Corrosion-Damaged Carbon Steel Tubular Members - Ahn, Jin-Hee (Materials (Basel), 2018)
Local corrosion damage of steel structures can occur due to damage to the paint-coated surface of structures. Such damage can affect the structural behavior and performance of steel structures. Compressive loading tests were, thus, carried out in this study to examine the effect of local corrosion damage on the structural behavior and strength of tubular members. Artificial cross-sectional damage on the surface of the tubular members was introduced to reflect the actual corroded damage under exposure to a corrosion environment. The compressive failure modes and compressive strengths of the tubular members were compared according to the localized cross-sectional damage. The compressive loading test results showed that the compressive strengths were affected by the damaged width within a certain range. In addition, finite element analysis (FEA) was conducted with various parameters to determine the effects of the damage on the failure mode and compressive strength of the stub column. From the FEA results, the compressive strength was decreased proportionally with the equivalent cross-sectional area ratio and damaged volume ratio.